2023
DOI: 10.1161/circgen.122.003924
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Previously Unrecognized RNA Splice-Altering Variants to Congenital Heart Disease

Abstract: BACKGROUND: Known genetic causes of congenital heart disease (CHD) explain <40% of CHD cases, and interpreting the clinical significance of variants with uncertain functional impact remains challenging. We aim to improve diagnostic classification of variants in patients with CHD by assessing the impact of noncanonical splice region variants on RNA splicing. METHODS: We tested de novo variants from trio studies of 2649 CHD probands and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“… 30 This finding has been replicated across multiple studies-with several different de novo loss-of-function mutations in RBFOX2 identified in probands with HLHS. 30 , 31 , 32 Although no published studies have identified molecular mechanisms in genetic animal models with human pathogenic mutations identical to those in humans, numerous animal experiments have demonstrated the necessity of RBFOX2 for heart development. Specifically, Rbfox2 loss in zebrafish resulted in HLHS-like phenotypes, characterised by a reduced ventricle size, abnormal myocardial segments, and mitochondrial defects.…”
Section: Splicing Factors and Cardiovascular Diseasementioning
confidence: 99%
“… 30 This finding has been replicated across multiple studies-with several different de novo loss-of-function mutations in RBFOX2 identified in probands with HLHS. 30 , 31 , 32 Although no published studies have identified molecular mechanisms in genetic animal models with human pathogenic mutations identical to those in humans, numerous animal experiments have demonstrated the necessity of RBFOX2 for heart development. Specifically, Rbfox2 loss in zebrafish resulted in HLHS-like phenotypes, characterised by a reduced ventricle size, abnormal myocardial segments, and mitochondrial defects.…”
Section: Splicing Factors and Cardiovascular Diseasementioning
confidence: 99%
“…10 Further, contributions from common variants toward the development of certain CHD subtypes, including transposition of the great arteries and other complex disease, have been highlighted. 11,12 In this edition of Circulation: Genomics and Precision Medicine, Jang et al 13 evaluate noncoding variants near canonical splice sites and their potential to disrupt RNA processing resulting in CHD. Using a combination of computational and in vitro (minigene) assays, they identified 53 de novo variants and 74 rare variants resulting in aberrant splicing in a cohort of 4474 CHD probands from the Pediatric Cardiac Genomics Consortium.…”
Section: See Article By Jang Et Almentioning
confidence: 99%
“…Over the last decade, following significant advances in genomic technology, we are beginning to piece together the complex puzzle of CHD etiology (Figure ), with the study by Jang et al 13 contributing another important piece. A significant portion of the remaining unsolved cases are hypothesized to result from complex interactions between multiple genetic/epigenetic changes and factors affecting the fetal-placental-maternal environment.…”
Section: See Article By Jang Et Almentioning
confidence: 99%
See 2 more Smart Citations